Formation of an Approach to Improving Regional Competitiveness in the Russian Federation - Grigory Kulkaev (Sustainable Development and Engineering Economics, 2024)
Today, in order to develop national economies, it is necessary to pay attention to the economies of the regions of the countries. The regional economy is the basis of the national welfare. In the Russian Federation there are a number of problems with regional development, one of which is the differentiated development of the constituent entities of the Russian Federation. Every year, the difference in development increases due to the rapid growth of large economic regions and the lag in regions removed from the central regions. In the context of such key competition factors, this development becomes competitive in the region. The article examines various concepts of and approaches to regional competitiveness that contribute to the formation of comprehensive economic cooperation. Through analysis of statistics on indicators of the socio-economic development of some regions of the Russian Federation, the reason for the observed disproportion was identified. This reason is the outflow of population. A person with strength and skills is a key part of building a regional economic system. To solve problems that arise in the work, a model for increasing regional competitiveness is proposed, which includes three stages. The first is basic, focusing on building the foundations of production; the second stage involves focusing on the development of science and education; and the third is creative, focused on the development of creative industries. Thus, the model proposed by the author meets the criterion of complexity, as well as the requirements for increasing the competitiveness of regions in the medium and long term, which will contribute to the socio-economic development of the constituent entities of the Russian Federation, balance and balance in the level of development of the country as a whole.